An Approach to Family Counseling - Sabar, Sabarrudin; Masril, Masril; Hael, Edar; Adolt, Searly (Yayasan Minang Darussalam, 2022)
Problems in the family must immediately be solved not to hurt the family. One solution to various problems in the family can be solved with the existing approach to family counseling so that the issues faced can be resolved. The purpose of this study was to determine the best approach for family counseling. This research was conducted in the form of a literature review using a database in the form of Google Scholar. The literature used is in English and Indonesian format within the last ten years and is fully accessible. The literature review research found approaches in family counseling, namely the family counseling approach according to Adler, the rational-emotive process, the passionate transactional method, the psychoanalytic approach, the behavioral approach, and the logotherapy approach.